The Effect Of Procedural Justice On Organizational Commitment In The Malaysian Context: Do Men And Women Differ? - Mohd. Nasurdin, Aizzat; Ahmad, Zainal Ariffin (Asian Academy of Management (AAM), 2001)
The purpose of this paper is to determine the influence of procedural justice on organizational commitment and whether gender differences play a role in moderating the above-mentioned relationship among Malaysian employees. Based on the social exchange framework (Blau, 1964), the norm of reciprocity (Gouldner, 1960), and the “ group-value” model (Lind & Tyler, 1988), a study was conducted among hotel workers in Malaysia. Analyses of 161 responses reveal that procedural justice does have a significant effect on organizational commitment. While gender does not moderate the effect of procedural justice on employees’ commitment, the findings may suggest a trend toward similarity in beliefs, values, and attitudes towards work among males and females in the Malaysian workforce. Implications for managerial practice and future research are discussed